ANALISA PENGARUH SERVICE RECOVERY TERHADAP KEPUASAN PELANGGAN PADA MASKAPAI LOW COST CARRIER DI INDONESIA - Adam Reynaldi; Teguh Ariebowo (Jurnal Pijar, 2023)
The intention of this research is to use quantitative methodologies to investigate how service recovery (interactional justice, distributive justice, and procedural justice) impacts the satisfaction of customers at Indonesian low-cost carriers. This study featured a total of 100 participants, all of whom faced a service failure at Yogyakarta International Airport between July 2022 and April 2023 and afterwards received service recovery. According to the findings of the study, at the same time, procedural justice, distributive justice, and interactional justice each have a considerable impact on the attributes associated with consumer satisfaction. Furthermore, the three independent factors had an influence on consumer satisfaction. According to the coefficient of determination, the three independent variables investigated in this research account for 30.9% of the variance in customer satisfaction. Meanwhile, the remaining 69.1% of the variance is impacted by variables not included in this research. Based on these findings, low-cost airlines should prioritize creating fairness in their service recovery mechanisms if they want to boost customer happiness.